2021
DOI: 10.3390/nu13062059
|View full text |Cite
|
Sign up to set email alerts
|

Grape-Seed Proanthocyanidin Extract Reverts Obesity-Related Metabolic Derangements in Aged Female Rats

Abstract: Obesity and ageing are current issues of global concern. Adaptive homeostasis is compromised in the elderly, who are more likely to suffer age-related health issues, such as obesity, metabolic syndrome, and cardiovascular disease. The current worldwide prevalence of obesity and higher life expectancy call for new strategies for treating metabolic disorders. Grape-seed proanthocyanidin extract (GSPE) is reported to be effective in ameliorating these pathologies, especially in young animal models. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 65 publications
3
15
0
Order By: Relevance
“…32 Other authors 33 have clearly shown that it is an important target tissue for GSPE doses similar to those assayed in our study. We did not find any change in the urea/creatinine ratio, indicative of renal function, in these aged rats in any of the treatments; 19 therefore, further studies are required to elucidate this point.…”
Section: Papermentioning
confidence: 65%
See 1 more Smart Citation
“…32 Other authors 33 have clearly shown that it is an important target tissue for GSPE doses similar to those assayed in our study. We did not find any change in the urea/creatinine ratio, indicative of renal function, in these aged rats in any of the treatments; 19 therefore, further studies are required to elucidate this point.…”
Section: Papermentioning
confidence: 65%
“…We showed that GSPE treatment improved some metabolic parameters of the ageing processes in 21-week-old female rats 18 and also in the same rats under a cafeteria diet challenge. 19 Aged animals had a standard response to satiating GSPE doses as in young animals. 18 They also reduced food intake during cafeteria treatment when administered GSPE.…”
Section: Introductionmentioning
confidence: 97%
“…RAW264.7 cells (2.0 10 5 cells/mL) were incubated in 96-well plates at 37°C for 24 h, then removed from the medium and exposed to different concentrations (25, 50, 100 μg/mL) of SBP solution for 4 h. Subsequently, 800 μmol/L of H 2 O 2 was added to sample groups and incubated for another 4 h. The positive control group was treated with 25 μg/mL of VC solution instead of SBP. The CCK-8 assay was used to determine the cell viability ( Sierra-Cruz et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sierra-Cruz et al used a cafeteria diet to induce obesity and evaluated the antiobesity effect of grape seed proanthocyanidin extract on aged rats at two time points (a 10-day preventive treatment prior to cafeteria diet and a simultaneous treatment with the cafeteria diet for 11 weeks). The results showed that simultaneous treatment with the extract and cafeteria diet effectively reduced body weight, total adiposity and liver steatosis, whereas the preventive treatment only reduced mesenteric adiposity [ 57 ]. Human evidence is important to verify the antiobesity effect of grape.…”
Section: Health Benefits Of Grapementioning
confidence: 99%